Hak Pengelolaan Tanah Ulayat Masyarakat Hukum Adat untuk Kepentingan Investasi (Management Rights of Customary Law Communities Ulayat Land for investment purposes) - Dian Cahyaningrum (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2022)
Ulayat land is of importance to customary law communities. Therefore, customary law communities need to continue controlling and defending it. However, customary land is also expected to be used for investment purposes through management rights originating from customary land. Consequently, this paper examines and aims to determine the regulation and implementation of management rights originating from customary land for investment purposes. This paper has both theoretical and practical uses. By using the normative juridical method, the results of the management rights originating from customary land are determined and must be registered. Communal lands with management rights can partner with investors, and customary law communities continue to control their customary lands after the partnership ends. It differs from ulayat land, whose management rights have not been determined. The ulayat land can work in partnership with investors, but the land will become state land after the land rights expire. Leasing is also impossible because it cannot be applied to ulayat land. Management rights can only be assigned to customary law communities whose existence has been recognized. Thus, local governments should have good intentions and actively make efforts to give recognition to indigenous peoples in their regions. Mapping and recording of customary land need to be continued. To strengthen ulayat rights, a draft law on the protection of the rights of indigenous and tribal peoples also needs to be ratified immediately. AbstrakTanah ulayat sangat berarti bagi masyarakat hukum adat, oleh karenanya penting bagi masyarakat hukum adat untuk tetap menguasai dan mempertahankannya. Namun tanah ulayat juga diharapkan dapat dimanfaatkan untuk kepentingan investasi melalui hak pengelolaan yang berasal dari tanah ulayat. Untuk itu tulisan ini mengkaji dan bertujuan untuk mengetahui pengaturan dan pelaksanaan hak pengelolaan yang berasal dari tanah ulayat untuk kepentingan investasi. Tulisan ini memiliki kegunaan teoritis dan praktis. Dengan menggunakan metode  uridis normatif, diperoleh hasil hak pengelolaan yang berasal dari tanah ulayat ditetapkan dan wajib didaftarkan. Tanah ulayat dengan hak pengelolaan dapat dikerjasamakan dengan investor dan masyarakat hukum adat tetap menguasai tanah ulayatnya setelah kerja sama berakhir. Beda halnya dengan tanah ulayat yang belum ditetapkan hak pengelolaannya. Tanah ulayat tersebut dapat dikerjasamakan dengan investor, namun menjadi tanah negara setelah hak atas tanahnya berakhir. Sewa menyewa juga tidak dimungkinkan berlaku untuk tanah ulayat. Hak pengelolaan hanya dapat ditetapkan kepada masyarakat hukum adat yang telah diakui keberadaannya. Untuk itu pemerintah daerah sebaiknya beritikad baik dan aktif melakukan upaya memberikan pengakuan terhadap masyarakat hukum adat di daerahnya. Pemetaan dan pencatatan tanah ulayat perlu terus dilakukan. Untuk memperkuat hak ulayat, rancangan undang-undang tentang pelindungan terhadap hak masyarakat hukum adat juga perlu segera disahkan.